Posisi Negara dalam Penegakan Syariat Islam dalam Perspektif Sejarah - Abd Rahim Yunus (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2016)
This article aimed to describe about Islamic nation and its law. Every Islamic nation in the world has different concepts about Islamic law. It was happened because they have different point view. Nowadays, there are two kinds of Islamic nation, they are formal Islamic nation and non-formal Islamic nation. A formal Islamic nation is like Saudi Arabiyah. Saudi Arabiyah’s leader called al-Malik. It shows that Saudi Arabiyah is a formal Islamic nation. They have a monarchy goverment system. This is different with Indonesia, because Indonesia is non formal Islamic nation, It has democracy goverment system and Republic nation. Indonesia as an Islamic nation has many Muslim societies. So, Indonesia is Islamic nation also, although Indonesia has Republic system. So many titles used to call leader of Islamic nation. It is like khalifah, amir, al-Malik, Sulthan, etc.